PEMBENTUKAN BADAN OTONOMI DI BIDANG KEKAYAAN INTELEKTUAL BERDASARKAN PERATURAN DAN PERUNDANGAN DI INDONESIA - Muhammad Insan Kamil (Jurnal De Lege Ferenda Trisakti, 2023)
This research aims to analyze the rules and regulations related to the establishment of an autonomous body in the field of intellectual property in Indonesia. In addition, this research also conducts a comparison with the form of intellectual property offices in ASEAN member countries and Japan. The research method used is literature study and comparative analysis. The data used in this research are rules and regulations related to intellectual property in Indonesia, ASEAN, and Japan. The results of this research are expected to provide a better understanding of the establishment of autonomous bodies in the field of intellectual property in Indonesia and its comparison with other countries in ASEAN and Japan.